Altered structural brain connectome in young adult fragile X premutation carriers. Issue 9 (27th February 2014) - Leow, Alex; Harvey, Danielle; Goodrich‐Hunsaker, Naomi J.; Gadelkarim, Johnson; Kumar, Anand; Zhan, Liang; Rivera, Susan M.; Simon, Tony J.
Abstract Fragile X premutation carriers (fXPC) are characterized by 55–200 CGG trinucleotide repeats in the 5′ untranslated region on the Xq27.3 site of the X chromosome. Clinically, they are associated with the fragile X‐Associated Tremor/Ataxia Syndrome, a late‐onset neurodegenerative disorder with diffuse white matter neuropathology. Here, we conducted first‐ever graph theoretical network analyses in fXPCs using 30‐direction diffusion‐weighted magnetic resonance images acquired from 42 healthy controls aged 18–44 years (HC; 22 male and 20 female) and 46 fXPCs (16 male and 30 female). Globally, we found no differences between the fXPCs and HCs within each gender for all global graph theoretical measures. In male fXPCs, global efficiency was significantly negatively associated with the number of CGG repeats. For nodal measures, significant group differences were found between male fXPCs and male HCs in the right fusiform and the right ventral diencephalon (for nodal efficiency), and in the left hippocampus [for nodal clustering coefficient (CC)]. In female fXPCs, CC in the left superior parietal cortex correlated with counting performance in an enumeration task. Hum Brain Mapp 35:4518–4530, 2014. © 2014 Wiley Periodicals, Inc.